Pure Red Cell Aplasia Encountered in a Tertiary Care Hematology Laboratory: A Series of Nine Distinctive Cases - Kala, Mansi; Das, Kunal; Baveja, Avriti; Raturi, Manish; Dhebane, Meghali; Ahmad, Sohaib; Mehrotra, Mansi (Journal of Laboratory Physicians, 2022)
Pure red cell aplasia (PRCA) is characterized by severe anemia with reticulocytopenia and bone marrow erythroblastopenia. The early erythroblasts are markedly decreased; however, in rare instances, they may be normal or raised in number. There are varied etiologies, namely congenital or acquired and primary or secondary. The congenital PRCA is known as “Diamond-Blackfan anemia.” Thymomas, autoimmune disease, lymphomas, infections, and drugs also may be familiar associates. However, the etiologies of PRCA are numerous, and many diseases/infections can be associated with PRCA. The diagnosis rests on clinical suspicion and appropriate laboratory workup. We evaluated nine cases of red cell aplasia, having severe anemia with reticulocytopenia. Nearly half of the cases showed adequate erythroid (> 5% of the differential count) but with a maturation arrest. The adequacy of the erythroid could confuse the hematologist and may even delay the diagnosis. Hence, it is empirical that PRCA could be considered a differential in every case of severe anemia with reticulocytopenia, even in the presence of adequate erythroid precursors in the bone marrow.
Keywords: Diamond-Blackfan anemia; red cell transfusion; erythroblasts; severe anemia